Technology or content: Which factor is more important in people's evaluation of artificial intelligence news? - Yifei Li; Mingyang Yu; Sichen Li (Telematics and Informatics Reports, 2022)
With the introduction of artificial intelligence, journalism has entered a whole new phase of automated content production. This paper analyzes the content evaluation and behavioral willingness of audiences towards different types of news written by human and computer through a 2*2 factorial experiment. The results indicate that people have a stronger behavioral willingness towards data-based news than non-data-based news generated by computer. While for news generated by human, people don't distinguish the types of news, but decide whether to read and share it based on the quality of the content. The public's inherent impression of AI technology is also shown in this study to moderate people's technical evaluation on behavioral willingness. Based on the research findings, the implications and suggestions are addressed accordingly.